Papillary fibroelastoma of the aortic valve in association with rheumatic heart disease: a case report. Issue 1 (December 2016) - Shi, Jun; Bai, Zhi-xuan; Zhang, Ben-gui; Guo, Ying-qiang
Abstract Background Papillary fibroelastoma (PFE) is a rare primary cardiac neoplasm that is usually discovered incidentally at autopsy or during cardiac surgery. PFE combined with rheumatic heart disease (RHD) is extremely rare, and only a few cases have been reported. Additionally, the growth rate of the tumor is unknown. Case Presentation Here, we present a very rare case of PFE of the aortic valve combined with RHD, which were identified in a female patient who survived for 5 years without surgical intervention, and who subsequently underwent successful surgical treatment. Conclusions PFEs may be generally slow-growing tumors, however, the better treatment of choice may be surgery because it produces good curative effects with very low risk of complications, while preventing serious disease consequences.